2023
DOI: 10.1002/phar.2758
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of P2Y12 receptor inhibitors

Abstract: Oral P2Y12 inhibitors are commonly prescribed for cardiovascular disease and include clopidogrel, prasugrel, and ticagrelor. Each of these drugs has its strengths and weaknesses. Prasugrel and ticagrelor are more potent inhibitors of platelet aggregation and were shown to be superior to clopidogrel in preventing major adverse cardiovascular events after an acute coronary syndrome and percutaneous coronary intervention (PCI) in the absence of genotyping. However, both are associated with an increased risk for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 134 publications
(308 reference statements)
0
3
0
Order By: Relevance
“…Therefore, most of the benefit related to tailored antiplatelet therapy is achieved in the first few months after PCI, which is consistent with previous studies that have shown a shorter DAPT as potential optimal management [20,21]. It is reasonable to assume that the efficacy and safety of DAPT may be maximized beyond a one-size-fits-all strategy by switching patients who are poor metabolizers to novel P2Y12 inhibitors, which can be effective regardless of the CYP2C19 genotype [22], and switching patients who are efficient metabolizers back to clopidogrel. Nevertheless, experts in the field have recognized the usefulness of genotype-guided strategies without endorsing its use in routine clinical practice.…”
Section: Introductionsupporting
confidence: 83%
“…Therefore, most of the benefit related to tailored antiplatelet therapy is achieved in the first few months after PCI, which is consistent with previous studies that have shown a shorter DAPT as potential optimal management [20,21]. It is reasonable to assume that the efficacy and safety of DAPT may be maximized beyond a one-size-fits-all strategy by switching patients who are poor metabolizers to novel P2Y12 inhibitors, which can be effective regardless of the CYP2C19 genotype [22], and switching patients who are efficient metabolizers back to clopidogrel. Nevertheless, experts in the field have recognized the usefulness of genotype-guided strategies without endorsing its use in routine clinical practice.…”
Section: Introductionsupporting
confidence: 83%
“…The presence of CYP2C19*2 and/or CYP2C19*3 mutation genes in patients with intermediate metabolizer and poor metabolizer suggested an impact on clopidogrel responsiveness, res-ulting in clopidogrel resistance. [30,31] Previous studies have also identified CYP2C19 gene polymorphism as predictors of clopidogrel resistance. [32][33][34] Application of Antiplatelet Drugs in Patients with Coronary Heart Disease in the Real World Currently, the prognostic benefit of dual antiplatelet therapy (aspirin and clopidogrel) following acute coronary syndromes (ACS) has been well established.…”
Section: Discussion Cyp2c19 Gene Impact On Platelet Functionmentioning
confidence: 99%
“…Ticagrelor, a non-prodrug, binds reversibly to the adenosine diphosphate (ADP) P2Y12 receptor, inhibiting platelets without demanding metabolic activation [18]. It has a shorter half-life and needs to be taken twice daily.…”
Section: Ticagrelormentioning
confidence: 99%